Characteristics of Composite Flour Made of Kidney Bean and Soybean - Merynda Indriyani Syafutri; Friska Syaiful; Eka Lidiasari; Parwiyanti Parwiyanti; Sugito Sugito; Erlita Indah Astari; Jery Mega Saputra (Journal of Applied Agricultural Science and Technology, 2023)
Kidney beans and soybeans have the potential to be developed because they contain good nutrient. Kidney beans and soybeans are sources of vegetable protein. One form of development of legume products is composite flour. The aim of this study was to analyze the physical and chemical characteristics of composite flour made of kidney beans and soybeans. The experiment was designed using Completely Randomized Design with nine treatments and each treatment was replicated three times. The factor investigated was formulation of composite flour made from kidney bean and soybean (90%:10%; 80%:20%; 70%:30%; 60%:40%; 50%:50%; 40%:60%; 30%:70%; 20%:80%; and 10%:90%). The swelling power, solubility, color, white degree, moisture content, ash, protein, fat, and carbohydrate content were analyzed. The results showed that the higher percentage of soybean flour caused a decrease on  swelling power, white degree, and redness of composite flour, but it increased the value of solubility, lightness and yellowness of composite flour. Composite flour with higher percentage of kidney bean flour had higher carbohydrate level, while composite flour with higher percentage of soybean flour had higher protein and fat content. The moisture contents of composite flour made of kidney bean and soybean were in accordance with the standard for beans flour products.